2016
DOI: 10.1177/0095327x15618654
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Marines’ Attitudes Regarding Cross-Cultural Capabilities in Military Operations

Abstract: Cross-cultural competence not only emphasizes building specific skill sets such as language proficiency or negotiation skills, but also on changing the military's attitudes to other cultures by emphasizing the value and importance of cultural skills for successful military operations. In contrast to developing cultural skills, the task of shifting cultural attitudes is a far more complex process. Using empirical data from a survey of 2,406 Marines, this paper seeks to identify some of the social, demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…65 One program had conducted a series of systematic learner analyses to identify individual differences associated with attitudes toward cultural capabilities and CCT. 66 They found that Marine officers valued intercultural training and skills more than did enlisted Marines, as did unique in that it provides a progressive curriculum over a sequence of career stages. 67 As a smaller Service, the Marine Corps may be better positioned to align curricula than the other military Services and was more systematic in assessing its efforts.…”
Section: Learner Analysismentioning
confidence: 99%
“…65 One program had conducted a series of systematic learner analyses to identify individual differences associated with attitudes toward cultural capabilities and CCT. 66 They found that Marine officers valued intercultural training and skills more than did enlisted Marines, as did unique in that it provides a progressive curriculum over a sequence of career stages. 67 As a smaller Service, the Marine Corps may be better positioned to align curricula than the other military Services and was more systematic in assessing its efforts.…”
Section: Learner Analysismentioning
confidence: 99%
“…Watkins & Sherk (2008) discuss the impact sociodemographic factors have on recruitment in the US military and draw links between these factors and the type of employment with which such individuals will naturally converge. This research is backed up by Holmes-Eber, Tarzi & Maki (2016) where their focus is the correlation between past experiences and future reactions to particular experiences. However, no such links were observed between those interviewed, the appointments they filled at home or on previous missions overseas and their selection as CIMIC officers on UN missions.…”
Section: Cimic -A National Perspectivementioning
confidence: 99%
“…However, only an appreciation of culture can be taught to an individual. As outlined by Hajjar (2010) and Holmes-Eber, Tarzi & Maki (2016), cultural awareness is a skill. Some people can adapt to a skill set better than others and so it is likely that this skill can only be properly developed by experience.…”
Section: This Point Was Also Backed Up By Io2;mentioning
confidence: 99%
“…Additionally, Section 833 calls for OMB to collaborate with Agency CIOs to establish standard metrics through which IT assessments can be achieved. It is also worth noting that through Section 833, FITARA calls for agencies to implement annual reviews of their IT portfolios [9]. It is also expected that agencies engage in a multi-year strategy that is updated and discussed to reduce and identify waste and duplication in their respective IT portfolios, a provision informed by the need to achieve cost savings [10].…”
Section: B Fitara Section 833mentioning
confidence: 99%
“…In the study by The technological issues or factors that the framework considers include global communications, intellectual property issues, technology patents, licensing and access, innovation potential technology legislation, consumer buying technology or mechanisms, information and communications, manufacturing capacity and maturity, technology maturity, the replacement of solutions or technology, research funding, and competing for technology development [9].…”
Section: ) Political Economic Social and Technological (Pest)mentioning
confidence: 99%